2020
DOI: 10.3390/molecules25092032
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic Profile of Croton urucurana Baill. Leaves, Stems and Bark: Pairwise Influence of Drying Temperature and Extraction Solvent

Abstract: Cerrado biome represents an area with great biodiversity. Some of its plants have significant ethnopharmacological uses, with specific purposes. Croton urucurana Baill., for instance, was previously acknowledged for its anti-hemorrhagic, anti-inflammatory, antiseptic, healing, and potentially antifungal and entomopathogenic actions. Nevertheless, the compounds supporting these empirical applications are still unknown. Accordingly, this work was designed to achieve a complete characterization of the phenolic pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…C. urucurana was previously investigated for the chemical composition of its leaves and stem bark. Different compounds were reported in this plant, including flavan-3-ols, proanthocyanidins (condensed tannins), flavonols, O -glycosides, hydroxyflavones, C -glycosides [ 14 , 27 ], alkaloids, terpenes, and phenolic acids [ 10 ], which were obtained with different extraction solvents. In the present study, comparisons with authentic standards identified some main compounds in the extract of the leaves of C. urucurana , despite the lack of information to confirm the identification of some low-abundance peaks (e.g., 1, 2, 3, and 4).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…C. urucurana was previously investigated for the chemical composition of its leaves and stem bark. Different compounds were reported in this plant, including flavan-3-ols, proanthocyanidins (condensed tannins), flavonols, O -glycosides, hydroxyflavones, C -glycosides [ 14 , 27 ], alkaloids, terpenes, and phenolic acids [ 10 ], which were obtained with different extraction solvents. In the present study, comparisons with authentic standards identified some main compounds in the extract of the leaves of C. urucurana , despite the lack of information to confirm the identification of some low-abundance peaks (e.g., 1, 2, 3, and 4).…”
Section: Resultsmentioning
confidence: 99%
“…Other compounds were tentatively identified based on UV spectra, supported by previous reports, but some compounds were not observed in the current extract. Alves et al [ 27 ] performed a more comprehensive phytochemical analysis of the leaves of C. urucurana . They identified different classes of flavonoids, such as condensed tannins (e.g., proanthocyanidins).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations